The Benefits and Challenges of Korean Firms in Establishing Inter-Firm Network with Suppliers in Malaysia - Wonik, Kim; Yusof, Raja Nerina Raja; Abdullah, Abdul Rashid; Leong, Yee Choy (International Journal of Asian Social Science, 2020)
This study aims to explore the benefits and challenges of the inter-firm network relationships between Korean firms as buyers and their suppliers. Since the influence and strategies of the inter-firm network of overseas Korean firms have not been satisfactorily explored yet, this study attempts to contribute to the body of knowledge by exploring the benefits and challenges of inter-firm network for Korean firms in Malaysia. The results of this study highlights seven benefits of Korean firms having inter-firm networks: improved lead time and availability, ease of communication, long-term relationship, lower stock holdings at Korean multinational corporations or other MNCs (end-user), routine material information, trust relationship, and information sharing. In contrast, Korean firms also face challenges which include difficulty in terminating partnership, high dependence on one company, buyers’ superiority over the suppliers, a network of different strengths of suppliers, and connecting with the business through an informal network. The study suggests practical implications to be anticipated by potential suppliers of Korean firms in developing successful supplier-buyer relationships.